2009
DOI: 10.1111/j.1461-0248.2009.01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for tropical forest biodiversity in a human‐modified world

Abstract: The future of tropical forest biodiversity depends more than ever on the effective management of human-modified landscapes, presenting a daunting challenge to conservation practitioners and land use managers. We provide a critical synthesis of the scientific insights that guide our understanding of patterns and processes underpinning forest biodiversity in the human-modified tropics, and present a conceptual framework that integrates a broad range of social and ecological factors that define and contextualize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
598
0
49

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 836 publications
(665 citation statements)
references
References 114 publications
(234 reference statements)
18
598
0
49
Order By: Relevance
“…Nonfungal sequences and sequences that could not be identified to phylum (3 % of the sequences) were removed prior to downstream analyses. Although there were no significant differences in the total number of observed fungal OTUs across land-use types (F (2,23) =2.43, p=0.11), or in diversity indices (Table 1), OTU abundance accumulated most rapidly in the regenerating forest and slowest in the oil palm plantation (Fig. 1) and, similarly, predicted richness using the Chao 1 estimator showed that predicted fungal richness is greatest in the regenerating forest and lowest in the oil palm plantation (Fig.…”
Section: General Fungal Community Compositionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nonfungal sequences and sequences that could not be identified to phylum (3 % of the sequences) were removed prior to downstream analyses. Although there were no significant differences in the total number of observed fungal OTUs across land-use types (F (2,23) =2.43, p=0.11), or in diversity indices (Table 1), OTU abundance accumulated most rapidly in the regenerating forest and slowest in the oil palm plantation (Fig. 1) and, similarly, predicted richness using the Chao 1 estimator showed that predicted fungal richness is greatest in the regenerating forest and lowest in the oil palm plantation (Fig.…”
Section: General Fungal Community Compositionmentioning
confidence: 92%
“…Tropical forests contain more than two-thirds of all terrestrial plant and animal species [1][2][3], but long-term prospects for their survival are uncertain, as more than half of the original extent of these forests has already been degraded by human land-use change and other perturbations [4]. Agricultural expansion continues to be the main driver of tropical deforestation [5] with more than one third of the global terrestrial land area currently under cultivation [6].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, dynamics of plant diversity in these reforested ecosystems are poorly understood. Gardner et al (2009) suggested that both spatial and temporal patterns of biodiversity are the dynamic product of interacting historical and contemporary human and ecological processes. Considering the central role of tropical forests in protecting and maintaining terrestrial biodiversity, it is important to clarify the responses of biodiversity in these ecosystems to interactions of typical anthropogenic legacies (e.g., land-use practices) and contemporary anthropogenic influences (especially for N deposition).…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing viability of dry tropical forests is also under serious threat 5 . These alterations affect ecosystems that are central to the stability of Earth's atmosphere and climate 6 , as well as key providers of economic goods and ecosystem services 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of human populations into tropical forest environments has seen the latter become some of the most threatened ecosystems in the world 2,3 : every day c. 320 km 2 of tropical rainforest is destroyed, significantly impacting human populations along with 135 plant, animal, and insect species 4 . The ongoing viability of dry tropical forests is also under serious threat 5 .…”
Section: Introductionmentioning
confidence: 99%